Macroeconomic’s effect on Islamic and conventional banking profitability: Evidence from Indonesian dual-banking system - Abidillah, Achmad Fadlil; Kasanah, Roisatun; Rusgianto, Sulistya (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This paper aims to analyze the effect of macroeconomic and global crisis variables on Islamic and conventional banking profitability, evidence from Indonesian dual-banking system. Methodology – Time-series data from 2008q1–2021q2 were analyzed using an Autoregressive Distributed Lag (ARDL) model. This method can describe both long run and short run equilibrium between banking profitability and macroeconomic variables. Findings – The results point out that in a long run model, sharia banking's profitability is more resistant to macroeconomics shock than conventional's. Then, in a short run model, sharia's ROA and conventional's ROA face different effects of economic growth, exchange rate, and global crisis. Sharia's NPM is more affected by macroeconomic variables than conventional's. Originality – This study used an ARDL model to develop a dynamic relation between macroeconomic variables and dual bankings profitability.